Pembaharuan Hukum Islam di Indonesia Studi Kasus CLD Kompilasi Hukum Islam - Author: Nurjihad (Jurnal Hukum IUS QUIA IUSTUM, 2004)
The development of Islamic Law (fikih) meets the needs of society which is called upon to resolve increasingly complex issues. This is to the benefit of the Islamic community.However the term benefit to the community cannot be understood outside of the context of the protection of the aim of Islamic law which place regulation as the parameters of "benefit". In order to achieve this, ulama (Islamic Scholar) from a number of disciplines proclaim a collective ijtihad (interpretation, jama'i) which is thusable to solve new legalproblemsas fairly as possible.